Crucial Role of ADAMTS13 Related to Endotoxemia and Subsequent Cytokinemia in the Progression of Alcoholic Hepatitis - Uemura, Masahito; Fujimura, Yoshihiro; Matsuyama, Tomomi; Matsumoto, Masanori; Takaya, Hiroaki; Morioka, Chie; Fukui, Hiroshi (IntechOpen, 2012)
None